2007
DOI: 10.1111/j.1751-3928.2007.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrences of Ore Minerals and Fluid Inclusion Study on the Kingking Porphyry Copper–Gold Deposit, Eastern Mindanao, Philippines

Abstract: The Kingking deposit is a gold-rich porphyry copper deposit and the southernmost deposit at the eastern Mindanao mineralized belt, Philippines. It is underlain by Cretaceous -Paleogene sedimentary and volcanic rocks that are intruded by mineralized Miocene diorite porphyries and by barren Miocene -Pliocene dacite and diorite porphyries. The main alteration zones in the deposit are the inner potassic zone and the outer propylitic zone. The biotite-bearing diorite and hornblende diorite porphyries are the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Eastern Mindanao is host to several precious metal -base metal mines and prospects (e.g. Sillitoe, 1989;Suerte et al, 2007;Imai et al, 2009;Sonntag et al, 2011) (Figure 2). The general tectonic grain in the minesite is NW-SE consistent with the general direction of the Philippine Fault Zone.…”
Section: Geologymentioning
confidence: 99%
“…Eastern Mindanao is host to several precious metal -base metal mines and prospects (e.g. Sillitoe, 1989;Suerte et al, 2007;Imai et al, 2009;Sonntag et al, 2011) (Figure 2). The general tectonic grain in the minesite is NW-SE consistent with the general direction of the Philippine Fault Zone.…”
Section: Geologymentioning
confidence: 99%
“…3). Suerte et al (2007) reported the occurrence of bornite clots/pods in the brecciated parts of the biotite diorite porphyry overprinted by K-silicate alteration. They occur together with the andesite and diorite fragments without associated stockworks of quartz veinlets (Fig.…”
Section: Outline Of Kingking Porphyry Copper-gold Depositmentioning
confidence: 99%
“…Ore minerals and fluid inclusions at the Kingking deposit were studied by Suerte et al (2007). In addition, Suerte et al (2007) reported the occurrence of bornite pods in the brecciated parts of the biotite diorite porphyry, overprinted by K-silicate alteration, together with volcanic rock and diorite fragments without associated stockworks of quartz veinlets. Bornite pods are also reported in the Endeavor porphyry copper-gold deposit in Northparkes, Australia (Lickfold et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the porphyry copper deposits that have been mined already such as the Batu Hijau deposit, there are still a number of porphyry-type deposits and prospects remaining undeveloped in the ASEAN region. Suerte et al (2007) present the occurrences of ore minerals and fl uid inclusion study on the Kingking porphyry copper -gold deposit, Mindanao, Philippines. They demonstrate that bornite solid solution and intermediate solid solution ( iss ) were deposited as primary phases.…”
Section: Prefacementioning
confidence: 99%
“…Most papers were presented at the AUN/SEED-Net eighth Fieldwise Seminar on Geological Engineering Field and the third International Symposium and Exhibition entitled "Contribution of Science and Engineering for Geo-Hazard and Geo-Resources Management Toward Sustainable Development" held on 3 -4 August 2006 at Yogyakarta, Indonesia. Three papers describe magmatic and hydrothermal systems of porphyry-type mineralization ( Idrus et al , 2007;Imai et al , 2007;Suerte et al , 2007 ), while seven papers including one short communication report on hydrothermal systems associated with gold mineralization ( Ariffi n & Hewson, 2007;Crisostomo et al , 2007;Harijoko et al , 2007;Jimenez et al , 2007;Syafrizal et al, 2007;Warmada et al , 2007 ). In addition, one paper discusses temporal evolution of island arc magmatism ( Polve et al , 2007 ).…”
mentioning
confidence: 99%